2019
DOI: 10.1111/oik.06688
|View full text |Cite
|
Sign up to set email alerts
|

Interaction motifs variability in a Mediterranean palm under environmental disturbances: the mutualism–antagonism continuum

Abstract: The nature and the strength of plant–frugivore interactions often vary along an antagonism–mutualism continuum and are highly influenced by the local ecological context (e.g. level of environmental disturbances). However, little is known concerning how the local ecological setting where plant–frugivore interactions take place affects the seed dispersal effectiveness (SDE) and, eventually, plant recruitment. This knowledge gap relates to the scarcity of empirical investigations on individual‐based plant–frugivo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 73 publications
1
29
0
Order By: Relevance
“…humilis ’ foraging by ungulate seed predators, enhancing thus seed survival and fruit removal by mutualistic animal associates ( Fig 7B ). Therefore, both, mutualistic and antagonistic partners that shape the interaction outcomes among individual plants lead to contrasting seed dispersal success [ 18 , 70 ], appearing to shape a complex web of direct and indirect effects which’s net effect is most likely dependent on the community context [ 52 ]. This outcome may be strongly dependent on initial population densities that would most likely alter the dynamics of the system, thus, the net effect of dispersal success, among other factors, will probably be a result of the abundance of different functional guild of frugivores (legitimate seed dispersers, pulp feeders and seed predators) [ 87 89 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…humilis ’ foraging by ungulate seed predators, enhancing thus seed survival and fruit removal by mutualistic animal associates ( Fig 7B ). Therefore, both, mutualistic and antagonistic partners that shape the interaction outcomes among individual plants lead to contrasting seed dispersal success [ 18 , 70 ], appearing to shape a complex web of direct and indirect effects which’s net effect is most likely dependent on the community context [ 52 ]. This outcome may be strongly dependent on initial population densities that would most likely alter the dynamics of the system, thus, the net effect of dispersal success, among other factors, will probably be a result of the abundance of different functional guild of frugivores (legitimate seed dispersers, pulp feeders and seed predators) [ 87 89 ].…”
Section: Discussionmentioning
confidence: 99%
“…badgers and foxes) are the most effective seed dispersers of C. humilis and P. bourgaeana [29,30], whereas wild ungulates can behave as seed predators or seed dispersers [29][30][31]. Therefore, a greater dispersal success of individuals bearing more fruits due to higher visitation of the most effective dispersers can be limited depending on whether ungulates behave mostly as dispersers or as seed predators [70]. Other environmental conditions derived from the micro (e.g.…”
Section: Plos Onementioning
confidence: 99%
“…2019 b ), consequently, networks with a greater number of different motifs would have a greater diversity of interactions (Jácome‐Flores et al. 2020). At the other level, a motif is composed of two or more positions that can be occupied by different species simultaneously (Appendix : Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Also, Jácome‐Flores et al. (2020) reported that some interaction motifs were associated with seed dispersal effectiveness in individual‐based networks. Therefore, the network motif profile offers a network fingerprint that can be very useful to compare network properties, and study the impact of environmental perturbations on ecosystem functions.…”
Section: Introductionmentioning
confidence: 99%